Soil Restoration Practices on Priming Effect Intensity and Carbon Fluxes - Abdourhimou Amadou Issoufou; Bachirou Hamadou Younoussa; Idrissa Soumana; Ali Mahamane (Applied and Environmental Soil Science)
The decomposition of soil organic matter (SOM) is one of the most important processes influencing the global carbon (C) cycle, the physicochemical characteristics of soils, and the mineralization of nutrients for plant growth and soil food webs. Yet, priming effects are considered to be large enough to influence ecosystem carbon fluxes. Here, we have tested the effects of soil restoration practices on priming effects and carbon fluxes. Our results suggest that indirect effects such as altered stabilization of older C associated with the increased inputs of fresh plant inputs (“priming”) add uncertainty to the prediction of future soil C responses. In addition, restoration influences the abundance and diversity of decomposers, as well as the soil microbial community, by inducing up to more CO2 emission with fresh millet straw addition in fresh state than the predecomposed one. Restoration had strongly increased the impact by up to 22.7%, while the priming effect (PE) mineralization did not increase. The latter of the nonrestored site was lower than that of the restored site by 14.9–22.7%; the lowest mineralization per unit carbon was recorded in the nonrestored site. Through the “4 per 1000” initiative, it has been very recently demonstrated that priming effects could have a noticeable impact on soil carbon sequestration. The study has revealed that the degraded soil played a dominant positive role in the soil organic carbon mineralization. Our results provide solid evidence that SOC content plays a critical role in regulating apparent priming effects, with important implications for the improvement of C cycling models under global change scenarios.